2019
DOI: 10.1042/bcj20190688
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis 4-COUMAROYL-COA LIGASE 8 contributes to the biosynthesis of the benzenoid ring of coenzyme Q in peroxisomes

Abstract: Plants have evolved the ability to derive the benzenoid moiety of the respiratory cofactor and antioxidant, ubiquinone (coenzyme Q), either from the β-oxidative metabolism of p-coumarate or from the peroxidative cleavage of kaempferol. Here, isotopic feeding assays, gene co-expression analysis and reverse genetics identified Arabidopsis 4-COUMARATE-COA LIGASE 8 (4-CL8; At5g38120) as a contributor to the β-oxidation of p-coumarate for ubiquinone biosynthesis. The enzyme is part of the same clade (V) of acyl-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…All together these results demonstrate that the loss of function of At1g24340 results in a metabolic blockage downstream of the formation of ubiquinone's ring, and confirm that At1g24340 acts as a ring modification enzyme. As previously observed for Arabidopsis mutants displaying similar losses in ubiquinone content (12,14), At1g24340 silenced plants were visually indistinguishable from their wild-type parent (data not shown).…”
Section: At1g24340 Knockdown Plants Display Impaired Ubiquinone Biosynthesis While Overexpression Of At1g24340 Does Not Boost Ubiquinone supporting
confidence: 85%
“…All together these results demonstrate that the loss of function of At1g24340 results in a metabolic blockage downstream of the formation of ubiquinone's ring, and confirm that At1g24340 acts as a ring modification enzyme. As previously observed for Arabidopsis mutants displaying similar losses in ubiquinone content (12,14), At1g24340 silenced plants were visually indistinguishable from their wild-type parent (data not shown).…”
Section: At1g24340 Knockdown Plants Display Impaired Ubiquinone Biosynthesis While Overexpression Of At1g24340 Does Not Boost Ubiquinone supporting
confidence: 85%
“…PAL catalyzes the conversion of phenylalanine (Phe) to trans-cinnamic acid, which is subsequently converted into benzaldehyde and other derived compounds through oxidative and nonoxidative pathways (1). In plants, PAL is involved in the biosynthesis of p-coumarate and kaempferol, both of which are precursors to 4-HB (17,18), and has been identified in some fungi of both Basidiomycota and Ascomycota, including Neurospora, Aspergillus, and Botrytis (14); however, this enzyme has not been identified in the Saccharomycotina subphylum. The formation of 4-HB in yeast and mammalian cells suggests that an unknown pathway exists (9).…”
mentioning
confidence: 99%
“…The substitution of the Cys from the box II motif towards a Trp would suggest these are not 4CL enzymes. However, recent reports on At4g19010 from subclade 3.4 (Block et al, 2014) and At5g38120 from subclade 3.3 (Soubeyrand et al, 2019) have unequivocally shown these to act as 4CL enzyme, albeit in a third pathway that, via the peroxisome leads to the synthesis of ubiquinone. Hence, we name these 4CL enzymes as class III 4CL enzymes.…”
Section: Discussionmentioning
confidence: 99%